What Now for China? - Zha, Daojiong (2016)
China has chosen not to take part in the arbitral tribunal brought against it by the Philippines. Hence, now that the tribunal has issued its ruling, China should stay away from commenting on the case and instead offer concrete plans for functional cooperation in the South China Sea.